The Relationship Between Mobile Legends Online Game Habits And Student’s Physical Fitness - Gunawan, Gunawan; Anggorowati, Kurnia Dyah (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This study aims to analyze the relationship between the habit of playing Mobile Legends online games and the physical fitness of STKIP Melawi students. The research hypothesis states that there is a significant relationship between Mobile Legends playing habits and students’ physical fitness levels. This research is motivated by the increasing intensity of online game use among college students which is often associated with sedentary behavior, but at the same time competitive games such as Mobile Legends also demand concentration, eye-hand coordination, reaction speed, decision-making, and team strategy involvement. The study used a quantitative approach with an ex post facto correlational design. The research sample amounted to 30 active STKIP Melawi students from the PGSD, PENJAS, and Mathematics Study Programs for the 2022–2024 batch who were selected through purposive sampling techniques with the criteria of actively playing Mobile Legends for at least three months. Gambling habit data was collected using a 20-item Guttman Scale questionnaire that included the dimensions of playing intensity, play patterns, physical impact, and physical activity. Physical fitness data was obtained through six tests, namely eye-hand coordination, vertical jump, T-Test agility, reaction speed, muscle endurance, and Bip Test/VO₂Max. Data analysis was conducted using Spearman Rank correlation. The results showed that the majority of students were in the category of high playing habits of 56.7%, with an average score of 14.27 out of a maximum score of 20. The average physical fitness score is 15.90 out of a maximum score of 30. The results of the correlation test showed a very strong and significant positive relationship between Mobile Legends playing habits and students’ physical fitness (r = 0.969; p < 0.001). Thus, the research hypothesis is accepted. These findings suggest that students with higher play habits tend to have better physical fitness in this sample, although the results need to be interpreted as a correlational relationship, not causality. Keywords: Mobile Legends; Physical Fitness; Students.